2017
DOI: 10.18869/nrip.jamsat.3.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Free testosterone and dehydroepiandrosterone sulfate serum levels in polycystic ovary syndrome women

Abstract: Objectives: This study designed to detect the prevalence of ovarian and/or adrenal hyperandrogenism in women with Polycystic Ovary Syndrome (PCOS). Materials:One hundred PCOS women included in this cross sectional study after informed consent and approval of the study by local institute ethical committee. Diagnosis of PCOS based on the Rotterdam ESHRE criteria. Studied women underwent complete physical examination with calculation of body mass index (BMI) and assessment of hirsutism by modified Ferriman Gallwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The results in table (1) show a significant increase differences in DHES when compared patients with control group compared at p < 0.001. These results were in agreement with some previous studies [11][12][13] Who showed the abnormally high levels of DHEA-S occur in about 20-30% of women with PCOS.…”
Section: Resultssupporting
confidence: 94%
“…The results in table (1) show a significant increase differences in DHES when compared patients with control group compared at p < 0.001. These results were in agreement with some previous studies [11][12][13] Who showed the abnormally high levels of DHEA-S occur in about 20-30% of women with PCOS.…”
Section: Resultssupporting
confidence: 94%
“…Mostafa et al reported manifestation of hyperandrogenism in 70% of PCOS women [5]. Mostafa et al in another study reported excess ovarian androgen in 50% of PCOS women and excess adrenal androgen (detected by DHEAs) in 30% of PCOS women [12].…”
Section: Discussionmentioning
confidence: 99%
“…Mostafa et al suggested measurement of free and total testosterone to detect the ovarian source of hyperandrogenism and measurement of DHEAs to detect the adrenal source of hyperandrogenism in PCOS women [12].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Mostafa et al , in another study reported excess androgen in 50% of PCOS women and they suggested the use of free and total testosterone to detect excess ovarian androgen production in PCOS. [10]…”
Section: Discussionmentioning
confidence: 99%